The state, law and workers' participation policies in Zambia, 1969-1989 : a study of the origins and development of law and participation policy in a developing country - Beele, Ernest Muketoi (1991)
This thesis is a study of the origins and development of law and workers' participation policies in Zambia from their inception in 1969 to 1989. The research was focussed at three levels of investigation: why was workers' participation introduced; what factors have determined its development; and whether the results suggest that state involvement, and the use of law in particular, has made a useful contribution to these industrial relations policies. The value of the work is threefold. First, it makes a modest but significant contribution to the understanding of law and industrial relations in post-independence Zambia. Second, it disputes and, in large measure, seeks to contradict earlier explanations thought to have determined the origins and development of participation policies in the country. Third, it provides original insights into the 1971 and 1988 workers' participation legislation. The methods of investigation have been largely historical and comparative. It analysed primary and secondary materials, supplemented by discussion interviews. Theoretical guidance was drawn from critical studies of corporations, labour law and industrial relations. The study reveals that the origins of workers' participation in Zambia is connected to the political objective in the 1960s of assuring the participation of Zambians in the ownership and management of the economy. Consequently, it argues that the development of these policies is best understood in the context of this origin as well as of the structures and institutions upon which they were erected in the 1970s. Turning to the assessment, it found that very little industrial relations effects have been demonstrated. This was partly a result of three interlocking factors. First, weak and inconsistent laws. Second, the failure to develop the widest possible consensus on participation policies. Third, the absence of economic and political conditions under which the confidence of managers and workers could be won towards state policies.